Turner's hypoplasia and non-vitality: A case report of sequelae in permanent tooth - P R Geetha Priya; John B John; Indumathi Elango (Wolters Kluwer Medknow Publications, 2010)
Hypoplasia is the result of disruption in the process of enamel matrix formation, which in turn causes defect in quality and thickness of enamel. Four cases of Turner's hypoplastic teeth with a previous history of trauma/infection in their primary predecessors at the age of 2-3 years have been reported. These hypoplastic teeth had turned non-vital without any carious insult, cavitation or further trauma. This article thereby stresses the importance of early detection of enamel hypoplasia and proper management at the earliest possible stage to enable an efficient prevention from clinically non-evident microbial invasion in the dentinal tubules and concomitant pulp pathosis.